Stress and stress coping in front of the higher education review: a style or process? - Quintana Peña, Alberto (1998)
We try to compare two theoretical-methodological approaches in order to identify factors that explain the dependent variables: evaluation stress and coping styles to this stress. On one side, Self theorists assume as independent variable of the evaluation stress the trait anxiety toward evaluation, and as independent variables of the coping stress styles the personal orientation (locus of control internal-external), and the cognitive style (dependence-independence of field). On the other side, theorists of behavior as process consider as independent variables of the first the cognitive evaluation of the exam and for the seconds tire stages of stress process (pre and post exam stages), The sample was 236 adolescents, of both genders, students of a pre-university academy, held by an university for direct acceptance, aged 16 to 18 years, selected by non probabilistic intentional sampling. Obtained results lead to the conclusion that the explanation about stress toward exams and the coping styles given for the theorists of behavior as process has more relationship with the facts than the given by self theorists.